STUDIES ON DIVERSITY OF INSECTS AT OHANKWU, NDUFU-ALIKE, IKWO L.G.A., EBONYI STATE NIGERIA - Ebele Okeke, Tobechukwu; Chukwu Nwanchor, Monday; Nwedufu, Chioma Jenifer; Ifeanyi Okpani, Sunday; Okey Umunnakwe, Emmanuel (SciencePlus, 2025)
Biodiversity is the variety of life, while biodiversity index quantifies differences in species composition and biomass within an ecosystem. This study examined insect diversity and abundance in Ohankwu, Ndufu-Alike, Ikwo L.G.A., Ebonyi State, Nigeria, from June to August 2024. Insects were sampled three times weekly (Monday, Wednesday, and Friday) using pitfall traps, sweep nets, light traps, and handpicking during morning and evening hours. A total of 1,748 insects belonging to 11 orders and 40 families were recorded across two sites. Out of these, 947 (54.18%) were collected from site 1, while Site 2 had 801 (45.82%). The identified orders included Blattodea, Coleoptera, Diptera, Hemiptera, Homoptera, Hymenoptera, Isoptera, Lepidoptera, Odonata, and Orthoptera. Hymenoptera had the highest relative abundance (54.28% in Site 1 and 53.93% in Site 2), followed by Blattodea (25.03% and 25.59%, respectively). Homoptera and Dictyoptera showed the lowest abundances (0.11% and 0.25%). Species composition differed significantly between sites (P = 0.001). Dorylus sp. (44.88%) was most abundant, followed by Macrotermes bellicosus (21.62%). Site 1 had a slightly higher Shannon–Wiener diversity index (2.16) than Site 2 (2.13), while Site 2 showed higher Margalef richness (9.12) and Simpson’s dominance (0.26). Both sites had equal evenness (0.52). These findings indicate that social insects are key contributors to ecosystem stability, influencing decomposition, soil aeration, and nutrient cycling. The study emphasizes the importance of conserving diverse habitats—such as farmlands, forests, and grasslands—and promoting organic farming practices to sustain insect biodiversity and ecosystem services while reducing dependence on pesticides